Relations between flexible work arrangements and employee performance in Serbian companies - Gašić Dimitrije; Berber Nemanja; Slavić Agneš; Bjekić Radmila; Aleksić Marko (Journal of Engineering Management and Competitiveness)
Flexible work arrangements (FWAs) represent a crucial phenomenon of today's digital society, where companies face various internal and external challenges that compel them to analyse and implement different forms of flexible work arrangements. These arrangements help companies to overcome challenges and positively influence employees' attitudes and behaviours. Employee performance refers to behaviour related to the efficiency and quality of task execution, including creativity, efficiency, productivity, accuracy, and overall contribution to company goals. High employee performance (EP) often results in a better business outcome, innovation, and competitive advantage for the company. This study investigates the relationship between flexible work arrangements and employee performance in companies from Serbia, utilizing a sample of 582 employees. The SmartPLS program was used for the analysis, employing the Partial Least Squares Structural Equation Modelling (PLS-SEM) method. The results indicate a positive direct effect of flexible work arrangements on employee performance. This finding underscores the significance of implementing flexible work policies to enhance productivity and overall performance in the workplace. The implications for management and policymakers are discussed, highlighting the potential benefits of adopting flexible work arrangements in the Serbian business context.